2011
DOI: 10.3109/09286586.2011.615449
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Retinopathy of Prematurity in a Large Tertiary Neonatal Intensive Care Unit in Turkey: Frequency and Risk Factors

Abstract: This is the largest prospective cohort study including infants younger than 34 weeks GA from Turkey. Our data which belongs to the last 1-year period shows lower incidence of severe ROP when compared to previous reports from Turkey. According to our data, screening babies smaller than 32 weeks GA or 1500g birth weight seems reasonable. In the presence of long duration of mechanical ventilation and PDA, screening should be intensified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
1
23
1
4
Order By: Relevance
“…An incidence of 32–47.27% has been reported previously from India 18 19 24. In recent studies from Iran and Turkey, incidences of 34.5% and 32.7% have been reported 20 21. Al Hazzani et al 13 reported an ROP incidence of 28.3% in a recent study carried out in Riyadh, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 98%
“…An incidence of 32–47.27% has been reported previously from India 18 19 24. In recent studies from Iran and Turkey, incidences of 34.5% and 32.7% have been reported 20 21. Al Hazzani et al 13 reported an ROP incidence of 28.3% in a recent study carried out in Riyadh, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 98%
“…It uses a probe with an operating frequency of 10 to 12 MHz and a linear amplification curve (4) . Retinopathy of prematurity (ROP) is a vasoproliferative retinopathy of infants who are born prematurely and with a low birth weight (5)(6)(7) . Moreover, ROP can be a potentially blinding condition (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Prematurely born children are disadvantaged in terms of perinatal mortality and long-term growth (3)(4)(5) , and they have low birth weight and shorter eyes as compared with full-term children (6,7) . …”
mentioning
confidence: 99%